Chronic malnutrition and cognitive performance - Paredes Arturo, Yenny Vicky (Universidad y Salud, 2015)
Objective: To describe the cognitive performance of a group of children with chronic malnutrition compared to a control group. Materials and methods: A cross-sectional correlational study, with no probabilistic intentional sampling was performed. The assessment of nutritional status was performed through anthropometry. A neuropsychological testing protocol for cognitive evaluation was applied by taking into account the parameters of weight and height. 76 children were included: 38 of them formed the case group (diagnosed with chronic malnutrition) and an equal number of subjects constituted the control group (without nutritional compromise). Results: Regarding the cognitive component, better performance in the control group in terms of subtests semantic fluency (p = 0.008) and figure of King (p = 0.044) was found. Likewise, the case group also had a higher performance on the subtest strikethrough figures regarding successes (p = 0.047) and omissions (p = 0.049). Conclusion: The case group evidenced some difficulties with verbal fluency and data processing; however improved performance was observed in attentional tasks. This leads to raise the need for further study of this subject, possibly oriented to the analysis of psychosocial variables, and other cognitive components.